Determinação da velocidade de infiltração pelo método do infiltrômetro de anel - Longhini Guerra , Heitor; De Castro Seron , Cassio; Pradi Vendruscolo, Eduardo; Battistuzzi Martins , Murilo; Vitória Alves Andrade, Lorena (ANAIS DO ENIC, 2026)
-